2022
DOI: 10.3390/ani12101308
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Single Neutrophil Extracellular Trap-Derived Components on Bovine Sperm Function

Abstract: Neutrophil extracellular traps (NETs) play a key role in fertilisation by eliminating microorganisms and entrapping spermatozoa in the female reproductive tract (FRT). The deleterious effects of NETs on spermatozoa have been previously described; however, individual exposure to NET-derived components in bull spermatozoa has not been explored. The aim of this study was to evaluate the effects of the main NET-derived proteins, histone 2A (H2A), neutrophil elastase (ELA), myeloperoxidase (MPO), pentraxin 3 (PTX),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…In this regard, very little is known about sperm-derived factors that promote NETotic cell induction and NET formation, while some studies suggest that it is the seminal plasma and not the sperm that triggers NETosis [ 31 ]. Conversely, other work suggests that it is an inherent property of sperm to induce this process, which is consistent with our observations [ 32 , 33 ]. The canine sperm in our model favors the formation of NETs, and it is still not entirely clear whether sperm motility would be a factor favoring PMN-derived NETosis.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In this regard, very little is known about sperm-derived factors that promote NETotic cell induction and NET formation, while some studies suggest that it is the seminal plasma and not the sperm that triggers NETosis [ 31 ]. Conversely, other work suggests that it is an inherent property of sperm to induce this process, which is consistent with our observations [ 32 , 33 ]. The canine sperm in our model favors the formation of NETs, and it is still not entirely clear whether sperm motility would be a factor favoring PMN-derived NETosis.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study demonstrated the individual damage induced by various NET proteins, including MPO, which is found in high concentrations in extracellular networks [ 9 , 38 ]. This membrane damage catalyzes the formation of a significant number of oxidative species [ 39 ], which can lead to further membrane lipid peroxidation in spermatozoa [ 32 ]. Similarly, our study demonstrated that MPO caused severe damage to the canine sperm membrane, where the acrosome was also affected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations